The reading and preaching of the scriptures in the worship of the Christian church : volume 2 : the patristic age - Old, Hughes Oliphant (Grand Rapids, Mich. : W.B. Eerdmans, 1998)
The Reading and Preaching of the Scriptures in the Worship of the Christian Church is a multivolume study by Hughes Oliphant Old that canvasses the history of preaching from the words of Moses at Mount Sinai through modern times. In Volume 1, The Biblical Period, Old begins his survey by discussing the roots of the Christian ministry of the Word in the worship of Israel. He then examines the preaching of Christ and the Apostles. Finally, Old looks at the development and practice of Christian preaching in the second and third centuries, concluding with the ministry of Origen.
V. 1: The biblical period -- The roots of the Christian ministry of the Word in the worship of Israel -- The preaching of Christ and the apostles -- The second and third centuries -- V. 2: The patristic age -- The flourishing of Greek preaching in the Christian empire--the school of Alexandria -- The Jerusalem lectionary in the fifth century -- The flourishing of Greek preaching in the Christian empire--the school of Antioch -- The Syriac church -- The Latin fathers -- The eternal Gospel in a dying culture -- V. 3: The medieval church -- Byzantine preaching -- The mission to the barbarians -- The shaping of the Roman lectionary -- The Benedictines -- The Cistercians -- The schools -- Franciscan preaching -- The Dominicans -- The German mystics -- The Czech Reform -- The preaching of nominalist pietism -- Preaching in Italy at the birth of the Renaissance --
Includes bibliographical references and index.
Keywords: Bible -- Homiletical use; Bible -- Liturgical use; Preaching -- History; Public worship -- History; History